Evaluation of the Effects of Food Safety Training on the Microbiological Load Present in Equipment, Surfaces, Utensils, and Food Manipulator’s Hands in Restaurants - Miguel Castro; Kamila Soares; Carlos Ribeiro; Alexandra Esteves (Biology and Life Sciences Forum)
Restaurants are a place were a lot of people go to have a delicious meal and have a good time however it is in the hands of the restaurant staff to provide a good environment and ensure the tasty meals are microbiologically safe. Food training comes a long way in this regard to help give that quality to the consumer but there are a lot of restaurants which workers do not have proper training for handling food or keeping the establishment’s food safe. This study revealed that in general there was more microbiological analysis non-compliant with food safety limits before the food safety training. After the training there was a reduction in the number of values exceeding the safety limits with reductions in microbiological load of above 80%.